2017
DOI: 10.1038/mp.2017.211
|View full text |Cite
|
Sign up to set email alerts
|

Secreted αKlotho isoform protects against age-dependent memory deficits

Abstract: αKlotho is a gene regulator of aging, increasing life expectancy when overexpressed and accelerating the development of aging phenotypes when inhibited. In mice, expression levels of the secreted isoform Klotho (s-KL) are very high in the brain, suggesting that s-KL activity may have an important role in the nervous system. Here we study the functional relevance at behavioural level of modifying s-KL levels in the aging brain. We used AAVrh10 vectors to deliver and sustained expression of s-KL in 6-and 12-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 37 publications
4
35
0
2
Order By: Relevance
“…The KL gene generates 2 transcripts in mammals, a full-length KL mRNA that encodes a single-pass 135-kDa transmembrane cell surface protein with extracellular KL1 (Glu34 to Phe506) and KL2 (Leu515 to Ser950) domains (designated mKL 135 ) (3). An alternative spliced mRNA that encodes only a KL1-like domain (sKL 70 ) is not translated in humans (4,5) but is found in the mouse brain (6,7). Rather, mKL 135 undergoes ectodomain shedding by ADAM10 (a disintegrin and a metalloproteinase domain 10) and ADAM17 metalloproteinases to generate a circulating isoform of about 130 kDa (sKL 130 ) that contains the KL1 and KL2 domains (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The KL gene generates 2 transcripts in mammals, a full-length KL mRNA that encodes a single-pass 135-kDa transmembrane cell surface protein with extracellular KL1 (Glu34 to Phe506) and KL2 (Leu515 to Ser950) domains (designated mKL 135 ) (3). An alternative spliced mRNA that encodes only a KL1-like domain (sKL 70 ) is not translated in humans (4,5) but is found in the mouse brain (6,7). Rather, mKL 135 undergoes ectodomain shedding by ADAM10 (a disintegrin and a metalloproteinase domain 10) and ADAM17 metalloproteinases to generate a circulating isoform of about 130 kDa (sKL 130 ) that contains the KL1 and KL2 domains (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Although short term incubation of slice cultures with shed KL did not affect synaptic transmission (Li et al 2017), shed KL did correct neural stem cell proliferation deficits (Laszczyk et al 2017). Increasing evidence suggests that extracellular forms of KL can influence brain function both within the central nervous system and from peripheral signaling (Leon et al 2017;Massó et al 2017). Although we do not fully understand KL proteins' function sufficient to attribute specific brain phenotypes to one or more forms, cerebrospinal fluid circulation of extracellular KL proteins (Imura et al 2004;Semba et al 2014;Kunert et al 2017) could allow broad effects of KL upon neurons.…”
Section: Shed Kl Reduces Bursting Kinetics Across Cultured Neuronal Nmentioning
confidence: 99%
“…The brain is reported to host all forms of KL protein: transmembrane, shed, and secreted (Shiraki-Iida et al 1998;Matsumura et al 1998;Imura et al 2004;Massó et al 2015;Massó et al 2017). Although short term incubation of slice cultures with shed KL did not affect synaptic transmission (Li et al 2017), shed KL did correct neural stem cell proliferation deficits (Laszczyk et al 2017).…”
Section: Shed Kl Reduces Bursting Kinetics Across Cultured Neuronal Nmentioning
confidence: 99%
“…We pioneered the exploration of Klotho's functions in the brain. Impaired cognition is observed in Klotho-deficient mice [5], while enhanced Klotho expression reduces cognitive deficits in a mouse model of AD [6] and improves cognitive functions in young [7] and old mice [8]. Recent work on Klotho's functions in the CNS, performed by us and by others, demonstrated that Klotho can combat processes associated with neurodegeneration through diverse mechanisms.…”
Section: Introductionmentioning
confidence: 97%